2013
DOI: 10.1186/1741-7015-11-57
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statins on testosterone in men and women, a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundStatins are extensively used for cardiovascular disease prevention. Statins reduce mortality rates more than other lipid-modulating drugs, although evidence from randomized controlled trials also suggests that statins unexpectedly increase the risk of diabetes and improve immune function. Physiologically, statins would be expected to lower androgens because statins inhibit production of the substrate for the local synthesis of androgens and statins' pleiotropic effects are somewhat similar to the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(151 citation statements)
references
References 60 publications
9
138
1
3
Order By: Relevance
“…This finding has now been corroborated by numerous subsequent studies [52]. It has also been reported that statins may reduce TT [53].…”
Section: Recommendation 3: Laboratory Diagnosissupporting
confidence: 75%
“…This finding has now been corroborated by numerous subsequent studies [52]. It has also been reported that statins may reduce TT [53].…”
Section: Recommendation 3: Laboratory Diagnosissupporting
confidence: 75%
“…A meta-analysis of five studies in men and six studies in women with polycystic ovary syndrome (PCOS) conducted by Schooling et al confirmed the hypothesis that testosterone levels in men decreased as a result of treatment with statins [14]. The results of the studies included in the meta-analysis were congruent.…”
Section: Other Parameterssupporting
confidence: 60%
“…Increasingly common, opioid analgesics can suppress the HPG axis centrally and peripherally, but the effects are short lived depending upon the half-life of agent used [Rajagopal et al 2004;Katz and Mazer, 2009]. Commonly used antihypertensive (β-blockers) and anticholesterol (statins) medications can induce mild to moderate reductions in serum testosterone levels [Rosen et al 1988;Schooling et al 2013]. Whether the medication, underlying medical condition, or both are at fault is unclear, but TD and comorbid medical conditions, and associated treatments can lead to a self-reinforcing cycle and development of TD symptoms.…”
Section: Etiologies Of Hypogonadism In Aging Menmentioning
confidence: 99%